2013
DOI: 10.1016/j.yhbeh.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Nongenomic effects of estradiol on aggression under short day photoperiods

Abstract: In several vertebrate species, the effects of estrogens on male aggressive behavior can be modulated by environmental cues. In song sparrows and rodents, estrogens modulate aggression in the nonbreeding season or winter-like short days, respectively. The behavioral effects of estrogens are rapid, which generally is considered indicative of nongenomic processes. The current study further examined the hypothesis that estradiol acts nongenomically under short days by utilizing a protein synthesis inhibitor, cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
3
17
0
1
Order By: Relevance
“…In control males, we observed that the number of AVP -ir cells in the BNSTmp was positively correlated with the number of bites, consistent with a previous study (Laredo et al, 2013). Male California mice that are cross fostered by the less aggressive white-footed mouse ( Peromyscus leucopus ) are less aggressive and have reduced AVP -ir staining in the BNSTmp (Bester-Meredith and Marler, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…In control males, we observed that the number of AVP -ir cells in the BNSTmp was positively correlated with the number of bites, consistent with a previous study (Laredo et al, 2013). Male California mice that are cross fostered by the less aggressive white-footed mouse ( Peromyscus leucopus ) are less aggressive and have reduced AVP -ir staining in the BNSTmp (Bester-Meredith and Marler, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Previous research shows that oestrogens increase aggressive behaviour in the nonbreeding season (4,7,(51)(52)(53)(54) and androgens and oestrogens are strongly implicated in dominance and aggression that occurs in the context of breeding. Several factors may explain this pattern of results.…”
Section: Effect Of a Short Dyadic Encounter On Neurosteroidsmentioning
confidence: 99%
“…Still, the impact of these compounds is generally under appreciated. As discussed above estrogens were found to increase aggression in Peromyscus when corncob bedding was used [45, 48], whereas estrogens decreased aggression when Carefresh was used [53, 56] (Fig 4). Previous work had determined that corncob bedding disrupts male and female sexual behavior in rats, and that this effect was mediated by THF-diols.…”
Section: Environmental Estrogens As Behavioral Disruptorsmentioning
confidence: 99%
“…California mice were housed under short days or long days and then castrated and treated with fadrozole. After recovery each mouse was injected with either saline or CX 1 hour before resident-intruder tests [53]. Thirty minutes before testing, mice were given an oral dose of cyclodextrin-encapsulated estradiol, cyclodextrin alone, or saline vehicle.…”
Section: Rapid Effects Of Estrogens On Behaviormentioning
confidence: 99%
See 1 more Smart Citation